The treatment of detergent industry wastewaters by supercritical water oxidation - Kipcak, Ekin; Senturk, Sema; Akgun, Mesut (SCIENTIFIC PUBL-INDIA, 2019)
This study presents the results of our research regarding the treatment of the detergent industry wastewaters by supercritical water oxidation. The experiments were carried out at a constant pressure. of 25 MPa, in the temperature range of 400-600 degrees C and in the reaction time range of 20-60 s. During the supercritical water oxidation of the wastewaters, hydrogen peroxide was used as the oxygen source. The effects of temperature, reaction time and oxidant use on the total organic carbon contents of the liquid effluents were examined. As a result, it was seen that supercritical water oxidation was a very effective method for the treatment of detergent industry wastewaters. Treatment efficiencies up to 97.8% in terms of total organic carbon conversion were achieved in very short reaction times.
Keywords: Detergent industry wastewater; supercritical water; oxidation; treatment; MILL WASTE-WATER; Chemistry